NEW Moon dates and coordinates - جواد حيدر; علي عبد الأمير (Iraqi Journal of Science, 2024)
The aim of the research is to make a simulation to the photon counting system for Crimean astrophysical observatory and south Africa astronomical observatory by arranged a theoretical tables of photon counting of each system which produced from the luminous flux arrived to the detector from different stars have various magnitudes using UBVRI filters system by take into account the limits of smallest magnitude for the systems.This tables can be used to indicates the precisions of data that registered by the observational system by compare the practical values with the theoretical simultaneously during the observation to determine the failure in order to be avoided